Infrared-spectra and normal-coordinate analysis of quinoline and quinoline complexes - Özel, Ayşen E.; Büyükmurat, Y.; AKYÜZ, SEVİM (Elsevier, 2001)
Normal coordinate analysis was performed on the vibrational spectra data of quinoline and the force field parameters of the free molecule were determined by the refinement of the corresponding parameters of benzene and pyridine molecules. The results of semiempirical (AM1) and ab initio (4-31G∗) calculations were taken into account during the refinement procedure. A partially common and well-transferable force field has been obtained for free quinoline. In order to investigate the coupling peculiarities of the vibrational modes of quinoline by metal–ligand vibrations, the calculated force field parameters of the free ligand were used in calculating the IR spectra of the transition metal (II) quinoline complexes, without any alterations and only force field parameters related to the M–N(Q) bond were introduced. The calculated spectra have been compared with the experimental spectra of the quinoline metal (II) complexes.
Keywords: Normal coordinate analysis; Force field refinement; IR spectrum; Quinoline; Complexes